If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 4F + -5N Solving 5 = 4F + -5N Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Add '-4F' to each side of the equation. 5 + -4F = 4F + -4F + -5N Combine like terms: 4F + -4F = 0 5 + -4F = 0 + -5N 5 + -4F = -5N Add '-5' to each side of the equation. 5 + -5 + -4F = -5 + -5N Combine like terms: 5 + -5 = 0 0 + -4F = -5 + -5N -4F = -5 + -5N Divide each side by '-4'. F = 1.25 + 1.25N Simplifying F = 1.25 + 1.25N
| 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 | | 12-2A-2B=0 | | 5+-26=18x | | 2=15x | | (x+8)(x-3)+30=0 | | 52=4x-4 | | -4/6f+1=-4 | | 7u+9u+u=140 | | 7y-2=13+10 | | 4z-2=2+7 | | 4x-9=6r-13 | | 7x=5x-18 | | 9mn+p=2k | | 10/2+1=6 | | -8(x+9)=-96 | | b^2+6b-x^2+9=0 |